Urea-based anticancer agents. Exploring 100-years of research with an eye to the future - Listro, Roberta; Rossino, Giacomo; Piaggi, Federica; Sonekan, Falilat Folasade; Rossi, Daniela; Linciano, Pasquale; Collina, Simona (Frontiers in Chemistry, 2022)
Suramin was the first urea-based drug to be approved in the clinic, and in the following century, a number of milestone drugs based on this scaffold were developed. Indeed, urea soon became a privileged scaffold in medicinal chemistry for its capability to establish a peculiar network of drug−target interactions, for its physicochemical properties that are useful for tuning the druggability of the new chemical entities, and for its structural and synthetic versatility that opened the door to numerous drug design possibilities. In this review, we highlight the relevance of the urea moiety in the medicinal chemistry scenario of anticancer drugs with a special focus on the kinase inhibitors for which this scaffold represented and still represents a pivotal pharmacophoric feature. A general outlook on the approved drugs, recent patents, and current research in this field is herein provided, and the role of the urea moiety in the drug discovery process is discussed from a medicinal chemistry standpoint. We believe that the present review can benefit both academia and pharmaceutical companies’ medicinal chemists to prompt research towards new urea derivatives as anticancer agents.